1997
DOI: 10.1002/marc.1997.030180912
|View full text |Cite
|
Sign up to set email alerts
|

Study of molecular size in ethylene‐propene copolymerization with zirconocene and hafnocene catalysts

Abstract: Ethylene-propene copolymerization was carried out with Cp2MC12 (Cp = cyclopentadienyl), r~c-Et(Ind)~MCl,, ra~-Me,Si(Ind)~MCl~ (Et = ethylene, Me2Si = dimethylsilyl, Ind = indenyl, M = Zr or Hf)/methylaluminoxane. In the case of using ansa-hafnocenes, the minimum molecular size (extended chain length) of ethylene-propene copolymer was obtained at about 50 mol-% of propene content in the copolymer. The polymerization activity decreased with increase of propene feed ratio in non-bridged non-specific metallocenes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…No significant change in similar propene‐ethene copolymers was reported by Sugano et al using bis(tetrahydroindenyl)zirconocene dichlorides 4. In contrast, Naga et al ( rac ‐[ethylene‐bis(η 5 ‐1‐indenyl)]ZrCl 2 )5 as well as Ziegler and co‐workers (ethylene‐bis(η 5 ‐1‐(4,7‐dimethylindenyl))metallocenes)6 found an increased molecular weight of propene‐ethene copolymers.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…No significant change in similar propene‐ethene copolymers was reported by Sugano et al using bis(tetrahydroindenyl)zirconocene dichlorides 4. In contrast, Naga et al ( rac ‐[ethylene‐bis(η 5 ‐1‐indenyl)]ZrCl 2 )5 as well as Ziegler and co‐workers (ethylene‐bis(η 5 ‐1‐(4,7‐dimethylindenyl))metallocenes)6 found an increased molecular weight of propene‐ethene copolymers.…”
Section: Introductionmentioning
confidence: 92%
“…One of the major parameters determining the mechanical properties is a sufficiently high molecular weight. A series of investigations have been published recently on this topic 3–6. However, their results are hardly comparable and come to different conclusions due to changes in catalyst structure, activation and process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that the increased rate cannot be explained by the faster rate of ethylene insertion, but were likely the result of the activation of dormant catalyst sites by ethylene. Some explanations have been forwarded to explain this phenomenon, including the trigger mechanism (Naga et al, 1997) and improved rates of diffusion due to the solubilization of active centers by the incorporation of comonomer (Koivumaki and Seppala, 1993). However, based on the study, it was suggested that the addition of diene would inhibit the attachment of ethylene to the active center resulting in decreased activity with increasing the E/P ratios.…”
Section: Fig 1 -Activity Profiles Of Ep Copolymerization With Varioumentioning
confidence: 98%
“…One interesting feature of certain metallocene catalyzed ethylene copolymerizations is the so called ''comonomer effect'', which is usually observed as an increase in the catalytic activity upon the addition of small amounts of comonomer. [1][2][3][4][5] Copolymer properties are also dramatically influenced by the presence of the comonomer, and several explanations have been suggested for this phenomenon. [6] During the last ten years, video microscopy has been introduced as a tool for investigating the kinetics of growing particles.…”
Section: Introductionmentioning
confidence: 99%